2015
DOI: 10.1007/s10544-015-9981-6
|View full text |Cite
|
Sign up to set email alerts
|

Silicon micromachined ultrasonic scalpel for the dissection and coagulation of tissue

Abstract: This work presents a planar, longitudinal mode ultrasonic scalpel microfabricated from monocrystalline silicon wafers. Silicon was selected as the material for the ultrasonic horn due to its high speed of sound and thermal conductivity as well as its low density compared to commonly used titanium based alloys. Combined with a relatively high Young's modulus, a lighter, more efficient design for the ultrasonic scalpel can be implemented which, due to silicon batch manufacturing, can be fabricated at a lower cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
3
16
1
Order By: Relevance
“…Some researchers selected the silicon to make the waveguide of ultrasonic scalpels, considering its superior mechanical and thermal properties. 6,16 However, the procedure to fabricate silicon is complex, and the produced micro-crack can lead to the failure of waveguide. Meanwhile, stainless steel is selected to fabricate the back slab, which can reduce the acoustic energy transmitted to the transducer's back end.…”
Section: Optimization Design and Dynamic Characteristics Analysis Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers selected the silicon to make the waveguide of ultrasonic scalpels, considering its superior mechanical and thermal properties. 6,16 However, the procedure to fabricate silicon is complex, and the produced micro-crack can lead to the failure of waveguide. Meanwhile, stainless steel is selected to fabricate the back slab, which can reduce the acoustic energy transmitted to the transducer's back end.…”
Section: Optimization Design and Dynamic Characteristics Analysis Of mentioning
confidence: 99%
“…Unlike high-frequency electric scalpels, ultrasonic scalpels rely on ultrasonic vibrations and ultrasonic energy to complete cutting and hemostasis of tissues. 5,6 Compared with high-frequency electric scalpels, ultrasonic scalpels significantly reduce the cutting-induced smoke and effectively keep the surgical field of view clear to avoid accidental injuries, especially when the surgical site locates close to major organs. 7 Moreover, the thermal damage to surrounding tissues caused by ultrasonic scalpels is much smaller than that caused by electric scalpels or laser scalpels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that the outcomes of ultrasonic dissection are associated with less tissue damage compared with electrosurgery [13][14][15][16]. However, their use is limited to a few fields of intervention due to the size, weight, and cost of the current systems [11,17,18]. This work aims to develop a new generation of ultrasonic microscalpel transducers for precision surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Other research [18,20,21] reported the development of a miniaturized planar ultrasonic scalpel design based on micromachined silicon. In contrast to a standard Langevin transducer [19,22,23] equipped with a stack of piezoelectric discs, piezoelectric plate actuators were used, mounted on both sides of the planar silicon structure and operated in its transverse resonant mode (d 31 ).…”
Section: Introductionmentioning
confidence: 99%